Urinary Exosomal Long Noncoding RNA TERC as a Noninvasive Diagnostic and Prognostic Biomarker for Bladder Urothelial Carcinoma. (25th January 2022) - Chen, Chen; Shang, Anquan; Sun, Zujun; Gao, Yuting; Huang, Jingjuan; Ping, Yili; Chang, Wenjing; Gu, Chenzheng; Sun, Junjun; Ji, Ping; Yuan, Yi; Lu, Renquan; et al.
Abstract : Purpose . Bladder cancer is one of the most common urological malignancies worldwide, and approximately 90% of bladder cancer cases are histologically typed as bladder urothelial carcinoma (BLCA). Exosomes are 30 to 200 nm extracellular vesicles that transport microRNAs, long noncoding RNAs (lncRNAs), mRNAs, circular RNAs, and proteins across tissues and through circulation. Urinary exosomes may contain genetic information from tumor cells. Herein, we explored the clinical significance of urinary exosomal lncRNA telomerase RNA component ( TERC ) levels to provide an urgently needed diagnostic and prognostic biomarker for BLCA. Materials and Methods . In this study, we used RNA-sequencing of samples from four BLCA patients and three healthy controls to identify that TERC was differentially expressed in urinary exosomes. We then used quantitative PCR in different types of clinical samples to validate the biomarker and analyzed results using receiver operating characteristic curves. Results . We found that TERC was significantly upregulated in urinary exosomes from BLCA patients compared with those from healthy controls (P < 0.0001 ). Urinary exosomal TERC showed higher sensitivity (78.65%) and accuracy (77.78%) than existing indicators including nuclear matrix protein-22 and urine cytometry. Using the cut-off value 4.302, the area under the curve for urinary exosomal TERC was 0.836 (95% confidence interval: 0.768–0.891, P < 0.0001 ). Furthermore, this noninvasive assay could distinguish low-grade and high-grade tumors (P = 0.0153 ). Conclusions . TERC is enriched in urinary exosomes from BLCA patients. Urinary exosomal TERC could become a diagnostic and prognostic biomarker for BLCA that allows clinicians to realize noninvasive detection of BLCA.